The effects of water and frequency on fatigue crack growth rate in modified and unmodified Polyvinyl Chloride - Samat, Noorasikin; Burford, Robert; Whittle, Alan; Hoffman, Mark (Wiley, 2010)
A study of the influence of water environments on the cyclic fatigue crack behavior of polyvinyl chloride (PVC), with (PVC-M) and without (PVC-U) chlorinated polyethylene (CPE) impact modifier was undertaken and compared with corresponding results in air. Two frequencies of 1 and 7 Hz were applied to assess the influence of frequency on the fatigue behavior; a higher fatigue resistance and threshold were obtained with increasing frequency. This trend is more significant in water. However, in this environment, the fatigue resistance deteriorated under conditions of higher stress intensity factor amplitude (ΔK) and frequency. The fatigue properties of PVC-U are the most affected by the presence of water, particularly at low frequency and higher ΔK. Examination of the fracture surface showed the interaction of water molecules and the PVC matrix with the formation of (1) a nodular structure, close to the fatigue threshold and (2) plasticized structures at high ΔK, which are associated with a greater threshold value and fatigue resistance. The absorption of the water retarded the fibrillation of craze and caused crack blunting effects. Water functions as a plasticizer, particularly at high ΔK, through the formation of the plasticized structures. Results are compared with those observed from an in-service failure